The Correlation Between Immunohistochemistry Findings and Metastasis in Squamous Cell Carcinoma: A Review. Issue 3 (3rd March 2021) - Lobl, Marissa; Grinnell, Madison; Phillips, Andrew; Abels, Joshua; Wysong, Ashley
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Cutaneous squamous cell carcinoma (SCC) is the second most common type of skin cancer. Only 2% to 5% of SCCs metastasize; however, those do carry a poor prognosis. Immunohistochemistry (IHC) is widely used by pathologists to characterize skin cancers and provide clinically useful information. OBJECTIVE: To evaluate the potential prognostic associations between IHC findings and metastasis in SCC. METHODS: Searches were conducted in MEDLINE via PubMed for articles published between 1999 and 2019. Search criteria included key words "immunohistochemistry" and "cutaneous squamous cell carcinoma." Six hundred and fifty-three articles were returned and screened, which ultimately left 31 for inclusion in our manuscript. RESULTS: Thirty-one articles analyzed in this review included a discussion of the expression of a particular IHC marker and the associated risk of metastasis and/or clinical utility of IHC markers in SCC, especially metastatic SCC. Markers that had several or more studies supporting clinical utility were E-cadherin, podoplanin, CD8 + T cells, PD-L1, epidermal growth factor receptor, and Cyclin D1. CONCLUSION: Immunohistochemistry profiling of SCC may be useful in select cases when providing a prognosis remains challenging and in identification of potential therapeutic targets for high-risk or metastatic tumors.